An Accurate and Reliable Computational Approach for the Mechanical Stress Analysis of Planar SOFC Stack. (2nd June 2015) - Fang, Xiurong; Li, Ang; Lin, Zijing
Abstract : Mechanical damage is a major factor limiting the long-term stability of SOFCs. It is a common practice to perform the stress analysis by isolating the interested component of an SOFC stack. This approach is questionable as it is difficult or even impossible to properly define the boundary condition for the isolated component. Here we show that the conventional approach is prone to provide misleading results. Grid settings are tested to reveal the grid dependence of the stress analysis results. A modest grid size is shown to be computationally efficient and satisfactorily accurate, allowing for the stress analysis of 20-40-cell stack by a desktop computer. Tests also show that the common practice with a free boundary condition for the interested component yields the maximal stress that is one order of magnitude too small.